Electron–phonon coupling in APd3O4: A = Ca, Sr, and Sr0.85Li0.15. (23rd December 2020) - Poojitha, Bommareddy; Reddy, B H; Joshi, Aprajita; Kumar, Ankit; Ali, Asif; Singh, R S; Saha, Surajit
Abstract: Here we have investigated the role of electron phonon coupling on the Raman spectrum of narrow bandgap semiconductors APd3 O4 ( A = Ca, Sr) and hole-doped system Sr0.85 Li0.15 Pd3 O4 . Four Raman active phonons are observed at room temperature for all three compounds as predicted by factor group analysis. The lowest energy phonon (∼190/202 cm −1 ) associated with Pd vibrations is observed to exhibit an asymmetric Fano-like lineshape in all the three compounds, indicating the presence of an interaction between the phonon and the electronic continuum. The origin of the electronic continuum states and electron–phonon coupling are discussed based on our laser power- and temperature-dependent Raman results. We have observed an enhanced strength of electron–phonon coupling in Sr0.85 Li0.15 Pd3 O4 at low temperatures which can be attributed to the metallicity in this doped compound.